PENGARUH LAMA PENYIMPANAN TERHADAP SIFAT FISIK DEDAK PADI - Febrina Grace Ivonne Marbun; Rahmat Wiradimadja; Iman Hernaman (JURNAL ILMIAH PETERNAKAN TERPADU, 2018)
The study aimed to determine the effect of storage time on the physical characteristics of rice bran. The study was carried out by the experimental method using a randomized block design with 5 treatments and 4 replications. The treatments used were the length of storage, namely 0, 1, 2, 3, and 4 weeks. The variables observed were the physical properties of rice bran which included specific density, bulk density, and compact bulk density and moisture content. The collected data was analysis of variance (ANOVA) and continued with the Duncan’s test. The results showed that the storage time from week 0 to week 4 did not have a significant effect on the specific density, bulk density, and compact bulk density. The treatment of each other had a significant effect (P <0.05) increasing the rice bran moisture content. It was concluded that the length of storage increased the moisture content with the regression equation y = 1.0963X + 8.728 with R2 = 0.7602, r = 0.8719, but did not affect the physical characteristics of rice bran. Keywords: Density, Moisture Content, Physical Characteristics, Rice Bran, Storage Time